Beyond the Clinical Perspective: A Conceptual Proposal for Social Risk Screening at Hospital Admission: https://doi.org/10.60543/ts_iss.vi10.11029 ("Temas Sociais" Journal, 2026)
Early identification of social risk factors in hospital settings has gained increasing attention as a strategy to improve continuity of care and reduce trajectories of clinical and social deterioration. However, its integration into care pathways remains uneven and conceptually insufficiently defined. This article presents a conceptual proposal for social risk screening at hospital admission, grounded in health social work and integrated care. It clarifies the distinction between social assessment, social screening and risk stratification, synthesises recent literature on the implementation of social risk screening instruments, and proposes a brief screening grid aimed at the early identification of situations of vulnerability that may affect hospital discharge and hospital-to-community transitions. The article also discusses the scope, limitations and ethical implications of the proposed model, emphasising that it is a conceptual framework that has not yet been empirically validated.
Keywords: Health social work; Social risk; Social screening; Hospital admission; Hospital-to-community transition